Pengaruh Metode Pembayaran, Discount, Dan Brand Ambassador Terhadap Keputusan Pembelian Scarlett Di TikTok Shop (Studi Kasus Pada Mahasiswa FEB Unisma Angkatan 2019) - Nia Wanda Kumala; Nurhidayah Nurhidayah; Abdullah Syakur Novianto (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research is conducted with the aim of examining the impact of payment methods, discounts, and the presence of brand ambassadors on purchasing decisions related to Scarlett products from the TikTok Shop. The study employs a quantitative research approach and focuses on students from the 2019 class at the Islamic University of Malang who have made at least one purchase of Scarlett products through the TikTok Shop. To ensure the quality of the research, validity and reliability tests have been conducted. The analysis of this study includes classical assumption testing, multiple linear regression analysis, statistical tests, and the calculation of the coefficient of determination. In this research, the independent variables consist of payment methods, discounts, and the presence of brand ambassadors, while the dependent variable is the purchasing decisions made regarding Scarlett products on the TikTok Shop. Keywords: Metode Pembayaran, Discount,  Brand Ambassador